Dyslipidaemia in the Middle East: Current status and a call for action. (September 2016) - Al Rasadi, Khalid; Almahmeed, Wael; AlHabib, Khalid F.; Abifadel, Marianne; Farhan, Hasan Ali; AlSifri, Saud; Jambart, Selim; Zubaid, Mohammad; Awan, Zuhier; Al-Waili, Khalid; Barter, Philip
Abstract: The increase in the cardiovascular disease (CVD)-associated mortality rate in the Middle East (ME) is among the highest in the world. The aim of this article is to review the current prevalence of dyslipidaemia and known gaps in its management in the ME region, and to propose initiatives to address the burden of dyslipidaemia. Published literature on the epidemiology of dyslipidaemia in the ME region was presented and discussed at an expert meeting that provided the basis of this review article. The high prevalence of metabolic syndrome, diabetes, familial hypercholesterolaemia (FH) and consanguineous marriages, in the ME region, results in a pattern of dyslipidaemia (low high-density lipoprotein cholesterol and high triglycerides) that is different from many other regions of the world. Early prevention and control of dyslipidaemia is of paramount importance to reduce the risk of developing CVD. Education of the public and healthcare professionals and developing preventive programs, FH registries and regional guidelines on dyslipidaemia are the keys to dyslipidaemia management in the ME region. Highlights: The pattern of dyslipidemia in the Middle East is different from other regions. Control of dyslipidaemia is important to reduce the risk of cardiovascular disease. Standardized definition and management guidelines for dyslipidaemia are needed. It is important to establish familial hypercholesterolaemia registry in the region.